Agincourt [compact disc, unabridged] - Cornwell, Bernard (Harper Audio, 2009)
Amidst the Hundred Years War, on October 25th, 1415, six thousand English troops defeated a French brigade comprising 36,000 men. Here, Cornell's main character Nicholas Hook narrates the astonishing story.